POLIGAMI DALAM PERSPEKTIF ISLAM - Misbachul Fitri, Abdul Basit; Nadhiroh, Lailatul (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2024)
The practice of polygamy has existed since before Islam came, and a husband could even marry up to a dozen women. This fact proves that the practice of polygamy continues to be maintained today with various justifications, social, economic and religious. In fact, polygamy has become part of a man’s lifestyle, which is why this practice has become entrenched in certain environments. If you look at polygamy in the Qur’an, there are three things that can be drawn, namely, giving men the opportunity to practice polygamy. Second, a warning to the husband to be able to act fairly. Third, there is the inability of men to behave fairly towards their wives even though they try hard. From these three points it can be concluded that one verse allows polygamy, while the other two verses seem to deny the realization of fair conditions.